MAPS: GEOGRAPHIC MAPS, CONCEPT MAPS (MIND MAPS) - putridamaiyanti yanti (CV Grasta Glory, 2026)
A map is a representation of the Earth's surface presented on a flat plane using scale, symbols, and a projection system to provide information about the condition of a particular area. Maps have an important role in human life because they help show the location of places, describe the condition of the Earth's surface, determine direction and distance, and support regional planning and learning activities. In addition to geographic maps, there are also concept maps or mind maps that are used to illustrate relationships between ideas, concepts, or information within a particular topic. Concept maps are usually arranged in the form of branching diagrams that begin with a main idea and then develop into several related subtopics. This paper aims to explain the definition of maps, the functions of maps, map elements, geographic maps, concept maps, and the differences between geographic maps and concept maps. The method used in this writing is a literature study by reviewing various books and relevant sources. The results of the discussion show that geographic maps are used to describe the condition and location of regions on the Earth's surface, while concept maps are used to help understand relationships between concepts in a subject. Therefore, both types of maps have different functions but are equally important as media for delivering information and supporting learning.